2019
DOI: 10.1088/1742-6596/1341/7/072015
|View full text |Cite
|
Sign up to set email alerts
|

α –Glucosidase inhibitory activity of breadfruit leaf extract (Artocarpus altilis (parkinson) fosberg)

Abstract: Breadfruit plant has been empirically used by the society as antidiabetic. The aim of this study is to understand the α-glucosidase enzyme inhibitory activity of bread fruit leaves (Artocarpus altilis) and their phytochemical profile. The varieties of leaf used were the yellow and green breadfruit leaves. Each was extracted with multiple maceration using n-hexane and 70% ethanol as solvents. From the phytochemistry identification, it was found that the ethanol extract of green breadfruit leaf contains alkaloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
1
0
2
Order By: Relevance
“…Similar results were also reported by Sikarwar et al (2015) where the only confirmed phytochemicals were flavonoids, steroids, tannins [15]. Among the five bioactive compounds that are expected to have analgesic properties confirmed to be present in breadfruit leaf extracts by many phytochemical determination studies are flavonoids [16,17].…”
Section: Treatments Parameterssupporting
confidence: 81%
“…Similar results were also reported by Sikarwar et al (2015) where the only confirmed phytochemicals were flavonoids, steroids, tannins [15]. Among the five bioactive compounds that are expected to have analgesic properties confirmed to be present in breadfruit leaf extracts by many phytochemical determination studies are flavonoids [16,17].…”
Section: Treatments Parameterssupporting
confidence: 81%
“…Another plant species Artocarpus altilis, commonly referred to as breadfruit and classified under the Moraceae family, is recognized for its richness in carbohydrates and diverse beneficial properties including antibacterial, antitubercular, antiviral, antifungal, antiplatelet, anti-arthritis, and antidiabetic activities. Ethanolic extract of these plant leaves exhibited significant α-glucosidase inhibitory activity [52].…”
Section: Medicinal Plants With Anti-diabetic Potential Used In Tradit...mentioning
confidence: 99%
“…Another plant species, Artocarpus altilis , commonly referred to as breadfruit and classified under the Moraceae family, is recognized for its richness in carbohydrates and diverse beneficial properties including antibacterial, antitubercular, antiviral, antifungal, antiplatelet, anti-arthritis, and antidiabetic activities. Methanolic extract showed α-glucosidase inhibitory activity with an IC 50 value of 40.9 μg/mL, whereas acarbose was used as a positive control with an IC 50 value of 964.6 μg/mL [ 26 , 52 ].…”
Section: Medicinal Plants With Antidiabetic Potential Used In the Tra...mentioning
confidence: 99%